Africa, NGOs, and the International Toxic Waste Trade - Jennifer Clapp (Journal of Environment and Development, 1994)
This article focuses on the involvement of Africa and environmental nongovernmental organizations (NGOs) in attempting to halt the international toxic waste trade. It shows that in addition to states, non-state actors have been important players in the international politics of the waste trade. An Africa-NGO alliance that formed in the late 1980s was able to influence the outcome of several international waste trade conventions. Despite regulations designed to keep waste imports out of Africa, waste traders were able to circumvent existing rules and continue their trade with the continent. In response to this persistence of the waste trade, a growing coalition ofenvironmental NGOs and developing country states has recently been successful in bringing about a global ban on the waste trade between Organization for Economic Cooperation and Development (OECD) countries and non-OECD countries. Whether or not this ban will be effective will depend to a great degree on the strength of the coalition of NGOs and states supporting the ban.